A Study on the Concept of Green Marketing and Green Product Development on Approach of Consumer Buying: Examining the Importance of Green Marketing and Green Product Development (Journal of Advances and Scholarly Researches in Allied Education, 2019)
With the ecological challenges becoming worse, the environmental interest of customers has contributed to a more diverse approach to consumer purchasing in the green lifestyle. Companies then take steps to improve potential environmental methods in the green business sector. Green marketing and green product creation are valuable techniques utilised by companies to improve their strategic edge and to meet the goal and vision of the company. Eco marketing and green product growth provide different advantages for companies in terms of raising environmental sustainability and raising consciousness about the company's name. This thesis reflects on the principle of green marketing and the production of green products and on the various consumption of green products, and finally explores the challenges companies face in failing to incorporate green marketing and green development.